2005
DOI: 10.1111/j.1365-2435.2005.01008.x
|View full text |Cite
|
Sign up to set email alerts
|

Functional linkages between leaf traits and net photosynthetic rate: reconciling empirical and mechanistic models

Abstract: Summary1. We had two objectives: (i) to determine the generality of, and extend the applicability of, a previously reported empirical relationship between leaf-level net photosynthetic rate ( A M , nmol g − 1 s − 1 ), specific leaf area (SLA, m 2 kg) and leaf nitrogen mass fraction ( N M , mmol g − 1 ); and (ii) to compare these empirical results with a mechanistic model of photosynthesis in order to provide a mechanistic justification for the empirical pattern. 2. Our results were based on both literature and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
97
2
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(106 citation statements)
references
References 54 publications
5
97
2
2
Order By: Relevance
“…the independent variable increase and the dependent variable decrease). to both a high leaf area displayed per unit mass invested (and hence efficient light capture) and high photosynthetic capacity (Reich et al, 1997(Reich et al, , 1999Shipley et al, 2005). Consistent with this general relationship, Franco et al, (2005) found that maximum net CO 2 assimilation increased with SLA for evergreen and deciduous species in the same area of this research.…”
Section: Plant and Stand-level Variation In Functional And Structuralsupporting
confidence: 73%
See 1 more Smart Citation
“…the independent variable increase and the dependent variable decrease). to both a high leaf area displayed per unit mass invested (and hence efficient light capture) and high photosynthetic capacity (Reich et al, 1997(Reich et al, , 1999Shipley et al, 2005). Consistent with this general relationship, Franco et al, (2005) found that maximum net CO 2 assimilation increased with SLA for evergreen and deciduous species in the same area of this research.…”
Section: Plant and Stand-level Variation In Functional And Structuralsupporting
confidence: 73%
“…Stem conductivity and total leaf surface area influence leafspecific hydraulic conductivity, a major determinant of leaf gas exchange capacity. Specific leaf area reflects properties of leaves as they are impacted by leaf water status and photosynthetic capacity (Reich et al, 1997(Reich et al, , 1999Shipley et al, 2005). To avoid the potential pitfalls of using correlations between scaling variables as indicators of causation, we established an a priori network of cause and effect relationships between biophysical, morphological and physiological traits of Neotropical savanna woody plants.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, after a serious insect attack occurred, damaged C. yedoensis contained larger quantities of material investment per unit area to perform a highly efficient anti-herbivore defense underrious insect attack. This high material investment per unit area is necessary to yield low leaf moisture and SLA, but high leaf thickness, single leaf wet weight, and single leaf dry weight compared with the results described in previous studies [7,[14][15]. Furthermore, leaves with low SLA contain more ructural carbohydrates, such as lignin and cellulose in their cell walls , than those with high SLA [23].…”
Section: Discussionmentioning
confidence: 61%
“…In this study, the following hypotheses were presented: 1) Leaf moisture and SLA of damaged leaves may be lower than those of healthy leaves; by contrast, leaf thickness, and single leaf wet and dry weight of damaged leaves may be higher than those of healthy leaves because damaged leaves should invest great biomass on leaf structures per unit area to exhibit a highly efficient anti-herbivore defense under seriuos insect attack. Furthermore, thick leaves or leaves with denser tissues contained greater dry biomass per unit area and lower SLA levels than thin leaves [14][15]. 2) Damaged leaves may display a higher phenotypic plasticity in leaf functional characteristics (SLA, as the preferred agent of plant growth and defense strategies) [7][8][10][11] than healthy leaves to develop a highly efficient anti-herbivore defense; this result could occur because the enhanced phenotypic plasticity for any functional characteristic could benefit plants by allowing these organisms to maximize fitness in the environment [16,17].…”
mentioning
confidence: 99%
“…Previous studies (Becknell and Powers 2014;Whitfeld et al 2014) also have reported either anomalous variation or increases in the CWM of leaf N, possibly due to an increase in the abundance of N-fixing species (Batterman et al 2013) or increases in soil pH. The expectation that leaf N will decrease during succession is predicated upon its positive correlation with A mass (Wright et al 2004), although recent studies have demonstrated that this relationship is also mediated by leaf structural attributes, density, and thickness, which comprise LMA (Poorter et al 2009;Shipley et al 2005Shipley et al , 2006. When controlling for variation in LMA, we found that correlations between leaf N and A mass for both size classes were conditionally independent (Online Resource 5).…”
Section: Successional Shifts In Functional Strategiesmentioning
confidence: 98%